Development of the main olfactory system and main olfactory epithelium-dependent male mating behavior are altered in Go-deficient mice - Choi, Jung-Mi (2016)
Fil: Choi, Jung-Mi. Ajou University School of Medicine. Department of Anatomy; Corea del Sur